Optimalisasi Usahatani Kentang Berbasis Kemitraan Di Desa Banjarejo Kecamatan Ngantang - Reza Aprillia Novita Sari; Bambang Yudi Ariadi; Yohana Agustina (SUAN PUBLISHER, 2026)
Indonesian agriculture plays a major role in the community's economy. Potatoes are one of the horticultural crops worth developing. The potato variety in this study is the Atlantic variety. Potato farming is a series of agribusiness processes that manage production factors aimed at obtaining financial profits. This commodity has high economic value and stable market demand. The objectives of this study were 1) to determine the characteristics of respondents, 2) to determine the optimal use of production inputs, 3) to determine the partnership collaboration carried out by PT. Indofood with potato farmers. The research data used were primary data using questionnaires and direct interviews, and secondary data through literature studies. The research location was in Banjarejo Village, Ngantang District. The data analysis method used the SPSS application, namely multiple linear regression and the calculation of the R/C ratio value. The respondents studied were 37 people. This study has the characteristics of respondents including those in the productive age range with an age range of 41-59 years. The independent variable of seeds has a significant effect on the amount of Atlantic potato production, the R/C ratio value is 1.12 > 1 so that Atlantic potato farming is feasible to be developed in Banjarejo Village, the partnership cooperation carried out by PT. Indofood with farmers is trade cooperation (market).